Some thermal and tectonic models for crustal melting in continental collision zones. - England, P; Thompson, A (Blackwell Scientific; Geological Society Special Publication, 19, 1986)
Calculated geotherms and the pressure-temperature-time (PTt) paths followed by rocks during continental thickening episodes are interpreted with respect to the volumes of crustal melt that may be formed during orogenesis in the absence of heat transfer by mantle-derived melts. Particular attention is paid to a tectonic history that may characterize wider orogenic belts, such as are represented most obviously at present by Tibet. This comprises a period of crustal thickening, followed by an interval during which the crust is thinned by extensional strain, rather than by erosion. The amount of crustal melt produced depends strongly on the amount of water (free, and in hydrated minerals) contained in the lower crust.-from Authors